Ávila 1517-1519, la fundación de un pasado legendario: La invención de san Segundo - Manuel Abeledo (E-Spania)
In 1595 Antonio de Cianca publishes his book Historia de la vida invención, milagros y traslación de San Segundo using, in the ancient meaning, “invención” as discovery in order to refer to the finding of the body of Ávila’s first bishop, that would have taken place in 1519 in a humble church in Ávila’s periphery. This work studies thoroughly the sources before Cianca about saint Segundo in order to arrive to a series of conclusions, but two stands out among them. On one hand, it is clear that the intention of the authorities was to use the saint as a way to intervene in the construction of the city’s legendary past. On the other, and unlike the impression left by Cianca, the aim of those authorities was not to publish a discovery but, on the contrary, to silent it in order to produce the illusion of an uninterrupted tradition that would go back to the first times of Christianism.